2002
DOI: 10.1111/j.1151-2916.2002.tb00491.x
|View full text |Cite
|
Sign up to set email alerts
|

Fracture and Fatigue Behavior at Ambient and Elevated Temperatures of Alumina Bonded with Copper/Niobium/Copper Interlayers

Abstract: Interfacial fracture toughness and cyclic fatigue-crack growth properties of joints made from 99.5% pure alumina partial transient-liquid phase bonded using copper/niobium/copper interlayers have been investigated at both room and elevated temperatures, and assessed in terms of interfacial chemistry and microstructure. The mean interfacial fracture toughness, G c , was found to decrease from 39 to 21 J/m 2 as temperature was raised from 25° to 1000°C, with failure primarily at the alumina/niobium interfaces. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 66 publications
(119 reference statements)
2
25
0
Order By: Relevance
“…In joints processed with 99.5%-pure alumina, examination of interfacial fracture surfaces was possible and revealed the presence of adherent islands of a silicide phase and tearing of niobium in bonded regions where the niobium was in contact with the finer-grain-size alumina regions [18,20,24]. This indicated that the small amount of glassy silicate phase present in the material may play a role in alumina-niobium contact formation and does modify the alumina-niobium interfacial microstructure.…”
Section: Mechanical Properties Of Assembliesmentioning
confidence: 99%
See 3 more Smart Citations
“…In joints processed with 99.5%-pure alumina, examination of interfacial fracture surfaces was possible and revealed the presence of adherent islands of a silicide phase and tearing of niobium in bonded regions where the niobium was in contact with the finer-grain-size alumina regions [18,20,24]. This indicated that the small amount of glassy silicate phase present in the material may play a role in alumina-niobium contact formation and does modify the alumina-niobium interfacial microstructure.…”
Section: Mechanical Properties Of Assembliesmentioning
confidence: 99%
“…Copper particles persist at the interface after bonding due to the low solubility of copper in niobium and a low rate of copper-niobium interdiffusion. These ductile particles affect the fracture strength of the joined assembly in a manner that depends specifically on the morphology and volume fraction of the copper [18,20,23,24]. The inset in Figure 1 shows two of these copper particles at increased magnification.…”
Section: Interface Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…The microstructure of these interlayer/alumina interfaces contained continuous and discrete second phase precipitates that resulted from a reaction between copper, alumina, and additional oxygen that was either dissolved in the copper or the niobium (this differs from the microstructure that developed in assemblies processed in a lower † p(O 2 ) environment [7][8][9]69 and is to be discussed later). The continuous precipitate was usually found at niobium grain boundaries and fracture often occurred through these precipitates.…”
Section: Prior Work On the Copper/niobium Systemmentioning
confidence: 99%